3D source tracking and error detection in HDR using two independent scintillator dosimetry systems. Issue 5 (28th March 2021) - Linares Rosales, Haydee M.; Johansen, Jacob G.; Kertzscher, Gustavo; Tanderup, Kari; Beaulieu, Luc; Beddar, Sam
Abstract : Purpose: The aim of this study is to perform three‐dimensional (3D) source position reconstruction by combining in vivo dosimetry measurements from two independent detector systems. Methods: Time‐resolved dosimetry was performed in a water phantom during HDR brachytherapy irradiation with 192 Ir source using two detector systems. The first was based on three plastic scintillator detectors and the second on a single inorganic crystal (CsI:Tl). Brachytherapy treatments were simulated in water under TG‐43U1 conditions, including a HDR prostate plan. Treatment needles were placed in distances covering a range of source movement of 120 mm around the detectors. The distance from each dwell position to each scintillator was determined based on the measured dose rates. The three distances given by the mPSD were recalculated to a position along the catheter ( z ) and a distance radially away from the mPSD ( xy ) for each dwell position (a circumference around the mPSD). The source x, y, and z coordinates were derived from the intersection of the mPSD's circumference with the sphere around the ISD based on the distance to this detector. We evaluated the accuracy of the source position reconstruction as a function of the distance to the source, the most likely location for detector positioning within a prostate volume, as well as the capacity to detect positioning errors. Results: Approximately 4000 source dwell positions were tracked for eight different HDR plans. An intersection of the mPSD torus and the ISD sphere was observed in 77.2% of the dwell positions, assuming no uncertainty in the dose rate determined distance. This increased to 100% if 1 σ search regions were added. However, only 73(96)% of the expected dwell positions were found within the intersection band for 1(2) σ uncertainties. The agreement between the source's reconstructed and expected positions was within 3 mm for a range of distances to the source up to 50 mm. The experiments on a HDR prostate plan, showed that by having at least one of the detectors located in the middle of the prostate volume, reduces the measurement deviations considerably compared to scenarios where the detectors were located outside of the prostate volume. The analysis showed a detection probability that, in most cases, is far from the random detection threshold. Errors of 1(2) mm can be detected in ranges of 5–25 (25–50) mm from the source, with a true detection probability rate higher than 80%, while the false probability rate is kept below 20%. Conclusions: By combining two detector responses, we enabled the determination of the absolute source coordinates. The combination of the mPSD and the ISD in vivo dosimetry constitutes a promising alternative for real‐time 3D source tracking in HDR brachytherapy.